Evaluación fisicoquímica, microbiológica y sensorial de una bebida láctea utilizando lactosuero y pulpa de guanábana - Demera Lucas, Edison Andres (2024)
The objective of this research was to evaluate the physical-chemical and microbiological effects of a dairy drink using sweet whey and soursop pulp. Three percentages of pulp were proposed (35%, 40% and 45%), which corresponded to the treatments. For the analysis of the physicochemical variables under study, a Completely Randomized Design (DCA) was proposed, which consisted of three treatments with five replicates each. For microbiological analyzes the NTE INEN 2304 (2008) standard for non-carbonated beverages was taken as a reference. The data of the physicochemical variables depending on the treatments were analyzed using the Kruskal Wallis nonparametric test, evidencing significant statistical differences (Sig. ≤ 0.05), where T1 (35% soursop pulp) stood out in the fat characteristics. with an average of 1.53% and 3.97% lactose and 2.82% protein, while T3 (45% soursop pulp) had better averages of pH (5.17), titratable acidity (0.72%) and °brix (11.13%). Treatments T1 (35% soursop pulp) and T2 (40% soursop pulp) presented acceptable results for fecal coliforms, yeast count, mold count, E. coli count and Listeria monocytogenes, while T3R3 (45% soursop pulp) showed the presence of E. coli, and was discarded. T2 (40% soursop) was the most acceptable in the attributes of flavor and color, with acceptance averages of 4.19 and 4.51 respectively, while T3 (45% soursop) presented the highest acceptability in smell (4.56) and texture (4.20).